2000
DOI: 10.1002/1096-9837(200008)25:8<847::aid-esp103>3.0.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

Mound development as an interaction of individual plants with soil, water erosion and sedimentation processes on slopes

Abstract: In the Mediterranean region, semi-natural shrubland communities (named`matorral') often present a discontinuous cover, where isolated perennial plants alternate with bare inter-plant areas. In such ecosystems, the patchy distribution of the vegetation is usually associated with microtopographic sequences of mounds that develop under isolated plants and break the overall slope continuity.In this study, the influence of three representative species of the Mediterranean matorral (Rosmarinus officinalis, Stipa ten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
78
0
7

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 127 publications
(92 citation statements)
references
References 20 publications
(31 reference statements)
4
78
0
7
Order By: Relevance
“…As regards banded patterns, the dynamics of spotted vegetation might be more complex, as the former usually act as closed hydrological systems and the latter highly depends on the connectivity of bare areas (Saco et al, 2007). Recent studies demonstrate that it is not only the extent to which vegetation patches prevail on a slope (Parsons et al, 1996;Wainwright et al, 2000;Bochet et al, 2000;Puigdefábregas, 2005) but also the connectivity of bare areas that influences hydrological processes such as runoff and sediment transport (Bautista et al, 2007;Puttock et al, 2013). Connectivity has the advantage, as regards vegetation structure, to provide an explanatory link between abiotic and biotic components to determine the hydrological and ecological function of the system (Turnbull et al, 2008(Turnbull et al, , 2010.…”
Section: Seed Removal By Runoff Influences the Origin Spatial Pattermentioning
confidence: 99%
See 1 more Smart Citation
“…As regards banded patterns, the dynamics of spotted vegetation might be more complex, as the former usually act as closed hydrological systems and the latter highly depends on the connectivity of bare areas (Saco et al, 2007). Recent studies demonstrate that it is not only the extent to which vegetation patches prevail on a slope (Parsons et al, 1996;Wainwright et al, 2000;Bochet et al, 2000;Puigdefábregas, 2005) but also the connectivity of bare areas that influences hydrological processes such as runoff and sediment transport (Bautista et al, 2007;Puttock et al, 2013). Connectivity has the advantage, as regards vegetation structure, to provide an explanatory link between abiotic and biotic components to determine the hydrological and ecological function of the system (Turnbull et al, 2008(Turnbull et al, , 2010.…”
Section: Seed Removal By Runoff Influences the Origin Spatial Pattermentioning
confidence: 99%
“…These water-limited landscapes frequently show a clear spatial pattern of vegetated patches interspersed within a bare soil matrix (Aguiar and Sala, 1999) which gives rise to a mosaic-like structure of sources and sinks of resources, the bare and vegetated patches, respectively, with very different soil properties and variable interconnection (e.g. Schlesinger et al, 1990;Ludwig and Tongway, 1995;Bochet et al, 1999Bochet et al, , 2000Puigdefábregas, 2005). Vegetated patches have often been com- Temporal evolution of the total number of papers on seed fate and dispersal in drylands published between 1974 and 2013, along with the evolution of the relative number of papers focusing on secondary seed dispersal.…”
Section: Introductionmentioning
confidence: 99%
“…Another common pattern is banded vegetation, also known as "tiger bush" in Africa and "mogotes" in Mexico, in which the dense biomass patches form bands, stripes or arcs (Aguiar and Sala, 1999;Ludwig et al, 1999;d'Herbes et al, 2001). Banded vegetation is usually aligned along contour lines and is effective in limiting hillslope erosion (Bochet et al, 2000). The bands favor soil conservation by acting as natural bench structures in which a gently sloping runoff zone leads downslope onto an interception zone .…”
Section: Processes Patterns and Functionmentioning
confidence: 99%
“…He found that infiltration rates are highest close to tree stems and decline rapidly with increasing distance. In many studies in arid areas, vegetation has been observed to be located in elevated mounds of a few centimeters height (Dunkerley, 2000, and references therein; Dunkerley, 1997;Bochet et al, 2000;Eldridge and Rosentreter, 2004). Greater infiltration rates in these elevated mounds (due to the presence of roots, soil fauna, etc) would therefore induce an increase in the apparent infiltration rates, as flow depth increases and inundates these higher areas within the groves.…”
Section: Overland Flow Dynamicsmentioning
confidence: 99%
“…The intercepted rainfall, diverted to leaf drip or stemflow, reached the soil surface with lower kinetic energy than the non-intercepted rainfall. The plant morphology seemed to be an important factor in intercepting rainfall and therefore in reducing soil loss and runoff (Bochet et al, 2000;Isselin-Nondedeu and Bédécarrats, 2007). That is, thyme knitted to the soil surface, forming a carpet of fine leaves and stems that restrained runoff and therefore soil sediments .…”
Section: Soil Loss and Runoff Response To Soil-management Systemsmentioning
confidence: 99%